2018
DOI: 10.1007/s10147-018-1338-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of neutrophil/lymphocyte ratio (NLR) and correlation with PET–CT metabolic parameters in small cell lung cancer (SCLC)

Abstract: There is relationship between PET-CT metabolic parameters and NLR in SCLC. Highest correlation was found with NLR and MTV, WBMTV, and WBTLG, and evaluation of NLR together with these parameters predicts survival times and tumor biology more clearly in SCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…In our present study, we determined that SUVmean also had a positive correlation with NLR. This result was consistent with previously reported findings [37]. However, the precise mechanism behind these correlations is complicated and is currently under investigation, but certain opinions may be useful for interpreting the mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…In our present study, we determined that SUVmean also had a positive correlation with NLR. This result was consistent with previously reported findings [37]. However, the precise mechanism behind these correlations is complicated and is currently under investigation, but certain opinions may be useful for interpreting the mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study conducted in 73 advanced HNSCC patients (Ohashi et al 2020 ) proved that WBC count was significantly correlated with 18 F-FDG PET/CT parameters, and speculated that tumor with upregulated aerobic glycolysis produce large amounts of lactic acid and cytokines and might mediate systemic inflammation via the lactic acid-induced IL-23/IL-17 pathway. Several studies also confirmed the relationship between PET-CT volumetric metabolic parameters and NLR/PLR in SCLC, NSCLC, cervical carcinoma and colorectal cancer (Du et al 2019 ; McSorley et al 2018 ; Mirili et al 2019 ; Wang et al 2020 ).…”
Section: Discussionmentioning
confidence: 78%
“…51,52 Also, some of the published studies were conducted in even smaller groups of participants. 44,51,53 Although some studies had a large number of patients, they didn't analyze patients separately considering disease extension. 54 It is important to note that the number of patients enrolled in the study was probably not adequate for the analysis of certain variables.…”
Section: Discussionmentioning
confidence: 99%